Piracy in Fashion Law: a paradox? - Rocha, Maria Victoria (2017)
The role of Law ought to be decisive in the protection of fashion products and their creators. Protection falls on immaterial goods, which are essentially protected by Intellectual Property, namely copyrights and industrial property rights, such as design (in the EU unregistred designs, special important for short cicle industries like fashion may be proected thanks to Regulation EC 6/2002 on protecting Community designs), trademarks and other distinctive signs, patents and utility models. Thanks to the digitalization and the Internet, there is a flourishing e-commerce related to fashion products, that competes with the traditional physical market. Almost every company sells in both markets and many sell only in the Internet. Thus, protection of domain names, and Websites or Facebook pages is very important because they function as the store open to the public, with its collections of goods, to which de consumers access on demand. It is important to protect these collections as databases. Protection must aslo occur against unfair competition. The rules against unfair competition play a very important roll in several ways, namely prevent trade-secrets, know-how, protect against acts of confusion, or prevent registration of industrial property rights thay may cause confusion. Also, when there is no protection by an exclusive right, either a copyright or an industrial property right, unfair competition rules may be the solution for protection. The fashion industry spends thousands in advertisment, thus advertisment rules also apply to fashion industry. Overlapping all these protections is also possible. The the EU Directive 98/71/CE, of the Parliament and the Council of 13th October 1998, about de protection of models and designs, imposes overlapping copyright with designs protected by Industrial Property, though we cannot say there is a satisfactory harmonization because the criteria are left for each State Member to decide, and the solutions are very different in each country. This Directive ought to be amended, but there are no strong lobbies for that to happen. In countries such the USA, there is no copyright protection of fashion because of its utilitary function. Only the strickly ornamental designs may be protected by copyrgight. There have been several bills to change the law, but they didn’t pass, until now, as far as we know. Fashion articles are largely copied by knockoffs and make alike industries, leading fashion originals industry to lose lots of money. Neverthelsss there are few lawsuits related to the copy of designs. The large number of lawsuits is related to copying trademarks and other distinctive signs. Imitation of original designs is a constant in the market, however it leads to the creation of a pyramid of markets of knockoffs, and doesn’t seem to cause damage. Nevertheless it implies new business models for the fist movers inorder not to be so affected by piracy. But not all the imitations of designs are acts of piracy, in many cases the knockoofs are inspired by top fashion companies and designers, but there is no copy in the legal sense of the work, what is copied is only a trend. Contrary to expectations, the fashion industry doesn’t seem to be affected, and is constantly adapting itself to imitation and piracy of designs. That’s why some authors call it the “Piracy Paradox”. Some authors say that piracy has led, in a certain way, fashion to reinvent itself, offer new products, and new models of business, thus leading to innovation and short fashion cicles. Although it may drive the creativity, the copy has affected some sectors of fashion. Fast fashion companies that make knockoffs, even before the original designs are sold, are most benefited by the practice, often hurting small highly qualified designers that don’t have ways to react. Aslo, fast fashion copying of original designers led some of these to lose money, and, in order to protect their designs, to use trademarks in the design, thus leading to less creativity, to sell bridge lines and to sell also very immediacy selling, and to create their own outlets. But the copying is not only bottom up, the haute couture maisons copy from one another in order to define trends. Though in the USA there is no copyright protection, contrary to what happens in the EU, where fashion designs may be protected by copyright, the behaviour of the companies seems the same, with some exceptions of emblematic lawsuits of great creators. And the doctrine and judges tend to be more demanding in what regards creativity, in order to protect fashion designs by Copyright. The low concentration of the highly fragmented fashion industry also contributes to weaken the protection because there are no strong lobbies to press law makers. The market is global, the laws are different, even within the EU, so the court rulings may be different according to the country where the lawsuit occurs and the law it applies. This leads to uncertainity, and there ought to be a large harmonization on this subject. Nevertheless, fashion industry flourishes. Is this a paradox? It seems to be so, but we don’t have the experience to see how fashion industry would behave, if there was a stronger global protection by Intellectual Property Laws, because it never happened until nowadays.